ANALISA TIME LAG SUHU PERMUKAAN LAUT YANG BERHUBUNGAN DENGAN CURAH HUJAN RATA-RATA DASARIAN DI PROVINSI BALI - Yadnya, I Made Sudarma; Tjahyo Baskoro, Winardi; Putra, M. Dwi Jendra (BULETIN FISIKA; Vol 16 No 2 (2015): BULETIN FISIKA, 2015)
Variability of rainfall a region often associated with global weather conditions, regional and local areas. Effect of local weather parameters such as sea surface temperatures (SST) around the island of Bali is still needs to be studied to determine its relationship with the average dasarian (accumulated ten days) rainfall variability of each regency/municipality in the province of Bali especially associated with the time lag. Value of correlation coefficient between the average dasarian of SST around Bali at time lag 0, -1 dasarian, -2 dasarian, and -3 dasarian with the average dasarian rainfall of each regency/municipality in the province of Bali is quite varies, where the lowest value of the correlation coefficient is 0.099 and the highest is 0.587. The average dasarian of SST around Bali island on time lag -1 dasarian have correlation values higher than the time lag 0, -2 and -3 dasarian. The sea surface temperatures of sea area Southeast and Southwest Bali island tend to have a fairly strong correlation with the average dasarian rainfall of each regency/municipality in Bali with an average value of correlation coefficients for each time lag ranging from 0.403 - 0.467 . Keywords : sea surface temperature, rainfall, time lag